Mengungkap Makna Kematian Soeharto pada Cover Majalah Tempo - Indiwan Seto Wahju Wibowo (Universitas Multimedia Nusantara, 2012)
Soeharto's death become a major topic of Tempo Magazine, issued No.50/XXXVI/04-10 February, 2008 specially in the magazine's cover. Nad this cover is so controversial as describes Soeharto as Jesus at the last super an iconic. Christianity symbol. The last super is the final meal that according to Christian belief, Jesus shared with his apostles in Jerusalem before his crucifixion. This research is about to describe what Tempo Magazine play their role as social control and it's rivalitation toward Soeharto. The purpose of this research is to find out the meaning behind the Tempo Magazine Cover as describes Soeharto – the former Indonesia – as Jesus. Kata kunci : makna kematian Soeharto, Semiotika Charles Sander Pierce, Kualitatif